Nutritional Transition Period In Early Larvae Marble Goby Oxyeleotris Marmoratus - Nguang, S. I; Ha, H.C. (2016)
The nutritional transition period of Oxyeleotris marmoratus were described based on the early development from hatching to 144 hours after fertilization (hAF) reared at 28-29oC. Long hatching period was observed with average hatching rate 70.1±13.2%. First hatching commenced at 24 hAF and continuous hatched until 96 hAF. The hatched larvae found developed coincide as the embryo developed. At 24 hAF, larvae hatched with unpigmented eyes and yolk (0.062±0.004 mm3 ) located below a straight digestive tract, mouth not opened and floated in water column. During endogenous nutrition phase, larval feeding system developed with their mouth and alimentary canal. Larval sensory organs have developed at 60 hAF, as the eyes begun pigmentation, olfactory pits opened and free neuromast with cupulae found on their head. At 84 hAF, first feeding on rotifer was observed as larvae possessed peristaltic intestine, opened anus, functional lower jaw and pectoral fin, and demonstrated horizontal swimming for foraging. This mixed nutrition phase occurred until 120 hAF when yolk completely absorbed. Due to the short nutritional transition period (84-120 hAF), phytoplankton and rotifers are suggested to provide to larvae before and during 84 hAF to enhance the larval survival.